Profetbog og billedsprog - Otzen, Benedikt (Religionsvidenskabeligt Tidsskrift, 1986)
Opposition delivered at the public defence of Kirsten Nielsen’s thesis “For et Træ er der Håb” (published Copenhagen 1985). The subtitle of the book announces its theme: the tree a metaphor in Isaiah 1-39. To the opposition is added a general introduction to the book. The criticism concentrates on the author’s use of the idea of “context” in her exegetical analysis of Is. 1-39.